Concentrated, Corporate, and Camouflaged: The Nature of AI News Coverage in Indonesia - Tuasikal, Rio; Gunawan, Virginia (Asian Journal of Media and Communication, 2024)
The adaptation of artificial technology in society requires a healthy public discourse. This necessitates nuanced and diverse views provided by mainstream media. However, there has not been empirical understanding of editorial practice towards AI in Indonesia, and whether news outlets have cited balanced voices. Drawing from a similar study in the United Kingdom, this paper seeks to identify the primary news sources and topics on the coverage of AI in Indonesian media outlets. This paper analyzed 777 news articles from January to June 2024, published by five major news sites namely Liputan6.com, Detik.com, Kompas.com, tvonenews.com, and Tempo.co. This paper found that of 1025 news sources, people representing the business sector dominated the conversation (55.6%), far beyond government (16.39%) and academics (13%). We also found that of 777 published articles, more than half discussed the AI industry itself (58.9%), compared to AI impact on society and labor (23.5%), and misuse and regulation (16.2%). We conclude that these media outlets have failed to provide varied viewpoints for the public, paving avenues for asymmetrical business-led debate, and allowing promotional messaging to camouflage as journalism reports.